Gadingsari maritime village: Empowerment of Gadingsari coastal communities through cultivation saline tilapia fish using biofloc technology - Khasanah, Staniya Uswatun; Subrata, Arsyad Cahya; Asephi, M. Yoga; Fadila, Salwa Ayu; Mahdi, Imam; Rahmah, Nur Aisyatul; Kurniaty, Maryani Atikah; Roazah, Qhusnul Fatimatur; Kusprihatini, Sita Alfia; Regina, Sona; Nugraheni, Renada Satya; Ahsan, Fahmi; Haikal, Rayhan Fiqri; Shalihah, Amilatun; Mutmainnah, Fadila Ainil; Mursalin, Ahza Durrani (Indonesia Berdaya, 2024)
The community empowerment program in Gadingsari Village through saline tilapia cultivation with biofloc technology aims to improve the skills and knowledge of the local community. This village has great maritime potential, but challenges related to education levels and lack of employment limit economic development. This program involves socialization, provision of biofloc equipment, distribution of fish seeds, and assistance in fish maintenance until harvest. Biofloc technology was chosen because it can optimize water and nutrient efficiency, and increase the yield of saline tilapia that is resistant to salinity conditions. R/C ratio analysis shows that the Biofloc system with a ratio of 1,38 is more profitable than the conventional system with a ratio of only 1,05. This program has succeeded in introducing new technology, increasing fisheries production, and providing a positive impact on the economic welfare of the local community.